Don't Get Above Your Raisin' (1984 -1996) (Ken Burns: Country Music., 2019)
As country music's popularity skyrockets, the genre confronts the question of whether it can also stay true to its roots. The success of the "New Traditionalists"--Reba McEntire, Randy Travis, the Judds, and Dwight Yoakam--suggests it can.